(untitled) (LACCEI, 2024)
The existing technological gap in the Covid 19 pandemic stage, shows that relevant aspects in education are sharpening, such as learning methodologies, processes and new technologies, which were of limited development before the year 2020, in such a way, that the objective of the research is to describe the existing technological gap and the academic performance of university students from 2010 to 2021. This article is the result of a systematic review process of authors, focused on the university environment. The findings show that despite the accentuated technological gap that is generated in times of pandemic, the academic performance of students was the same or better, however, connectivity in educational platforms and internet access has been an inconvenience that has been It manifests in a greater proportion according to socioeconomic level and geographical areas, however, the teaching-learning process had favorable and unfavorable fluctuations, leaving a field pending analysis in future research